Implementasi Text Recogniter yang Diterjemahkan ke Bahasa Lain dengan Firebase Ml-Kit Berbasis Android - Muclis, Pascal Aditia; Somantri, Somantri (Jurnal Informatika Universitas Pamulang, 2021)
Each community area has information, announcements and news made in a picture, pamphlet or poster. However, there are a lot of foreign languages in the information that are not understood by most people because of the lack of literacy in foreign language learning for the community, for that the author makes research on text recognition. Recognition or detection of text characters is also known as optical character recognition (OCR), which converts handwritten or printed text into data that can be edited and read by the system. After the text is converted into written form, the text is then converted from a foreign language (English) and then converted become Indonesian. This study uses observation and literature study in collecting information and materials for research, while for the method of making the system using prototyping which the system can be developed more quickly. The results of this application can help the people of Gunungendut Village to overcome the problem of understanding foreign language info that is in the image so that it is easy to understand using a mobile application.